Language Brain Representation in Bilinguals With Different Age of Appropriation and Proficiency of the Second Language: A Meta-Analysis of Functional Imaging Studies - Cargnelutti, Elisa; Tomasino, Barbara; Fabbro, Franco (Frontiers in Human Neuroscience, 2019)
Language representation in the bilingual brain is the result of many factors, of which age of appropriation (AoA) and proficiency of the second language (L2) are probably the most studied. Many studies indeed compared early and late bilinguals, although it is not clear the role of the so-called critical period for L2 learning. In this study, we carried out coordinate-based meta-analysis to address this issue and to inspect the role of proficiency besides that of AoA. After the preliminary inspection of the early (also very early) and late bilinguals’ language networks, we explored the specific activations associated with each language and compared them within and between the groups. Results confirmed that the language network associated with L2 was wider than that associated with L1 irrespective to AoA, although differences were more relevant in the late bilinguals’ group. In particular, L2 entailed a greater enrollment of the brain areas devoted to executive functions, and this was observed also in proficient bilinguals.. Also the early bilinguals showed a wide language network and as well activated areas involved in cognitive control. Interestingly, these regions activated even in L1 of both early and late bilinguals groups, although less consistently. Overall, these findings suggest that bilinguals in general are constantly subjected to cognitive effort to monitor and regulate the language use, although early AoA and high proficiency are likely to reduce it.